Tracing the development outcomes of agricultural investments in six research locations in Tanzania and Uganda: Questionnaire survey design and sample characterisation - Helle Munk Ravnborg; Bernard Bashaasha; Rikke Brandt Broegaard; Michael Byaruhanga; Evelyne Lazaro; Festo Maro; Khamaldin Daud Mutabazi; Teddy Triza Nakanwagi; David Tumusiime (Danish Institute for International Studies (DIIS), 2021)
This paper describes a questionnaire survey conducted as part of the Agricultural Investors as Development Actors (henceforward AIDA) research programme to establish the development outcomes of selected foreign agricultural investments for people living in the vicinity of such investments in six research locations, three in Tanzania and three in Uganda.
Keywords: 330; Water governance; Food and agriculture; Land rights and investments; Climate change and environment; Inequality and poverty; Development in practice; Global economic governance; Emerging economies